2021
DOI: 10.1155/2021/8855718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Major Reproductive Disorders in Dairy Cattle in and around Bale Robe, Oromia Regional State, Ethiopia

Abstract: A cross-sectional study by employing a questionnaire survey was conducted to determine the prevalence of major reproductive disorders in dairy cattle and its associated risk factors in and around Bale Robe town from November 2016 to April 2017. Out of 384 dairy cows which were under investigation, 254 (66.15%) had encountered at least one of the reproductive disorders. The major reproductive disorders recorded with high prevalence in the present study included mastitis (20.57%), repeat breeder (17.71%), retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…A similar prevalence has also been reported in northeast India [36]. Te prevalence observed in this study is lower than that determined by Tolosa et al [37], who reported a prevalence of the reproductive problem of 66.2% in Bale Robe. Te production system, breed, and environmental factors that could be seen in various locations could be attributed to this variation in prevalence.…”
Section: Occurrence and Associated Risk Factors Of Major Reproductive...supporting
confidence: 86%
“…A similar prevalence has also been reported in northeast India [36]. Te prevalence observed in this study is lower than that determined by Tolosa et al [37], who reported a prevalence of the reproductive problem of 66.2% in Bale Robe. Te production system, breed, and environmental factors that could be seen in various locations could be attributed to this variation in prevalence.…”
Section: Occurrence and Associated Risk Factors Of Major Reproductive...supporting
confidence: 86%
“…1.05 -5.889 However, the occurrence of reproductive problems was statistically insignificant with respect to parity, age at first calving, breeding method, farming system and age at maturity (p>0.05). The overall incidence of reproductive disorders in this study and the identified risk factors were also reported earlier (Tolosa et al 2021). The presence of reproductive disorder of any kind exerts its negative effect on farms.…”
Section: Risk Factors For Reproductive Health Problemsupporting
confidence: 86%
“…Many authors report the impact of abortion on dairy reproductive performance in different parts of the country. A much higher (28.9%) abortion rate was reported by Siyoum et al (Siyoum et al 2016), whereas Abunna et al (Abunna et al 2018) and Tolosa et al (Tolosa et al 2021) reported 8% and 4.1%, abortion rate respectively, in different breeds and farm settings. The presence of abortion in a dairy farm extends the calving interval which largely affects the profit of the dairy farm.…”
Section: Major Reproductive Problems Encounteredmentioning
confidence: 77%
See 1 more Smart Citation
“…This poses distinctive challenges for developing countries with expansive agricultural systems and remote areas [ 2 ]. The absence of up-to-date monitoring information on cattle reproductive health has adverse effects on livestock productivity [ 3 ]. In countries like Ethiopia, reproductive issues are emerging as significant concerns in cattle production [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%